Red Phosphorus Potassium‐Ion Battery Anodes - Chang, Wei‐Chung; Wu, Jen‐Hsuan; Chen, Kuan‐Ting; Tuan, Hsing‐Yu (Advanced science, 2019)
Phosphorus (P) possesses the highest theoretical specific capacity (865 mA h g−1) among all the elements for potassium‐ion battery (PIB) anodes. Although Red P (RP) has intrinsic advantages over its allotropes, including low cost and nontoxicity, and simpler preparation, it is yet unknown to effectively activate it into a high‐performance PIB anode. Here, high‐performance RP PIB anodes are reported. Two important factors are found to facilitate RP react with K‐ions reversibly: i) nanoscale RP particles are dispersed evenly in a conductive carbon matrix composed of multiwall carbon nanotubes and Ketjen black that provide an efficient electrical pathway and a tough scaffold. ii) The results of X‐ray photoelectron spectroscopy spectrum and the electrochemical performance perhaps show that no PC bond formation is beneficial to allow K‐ions to react with RP effectively. As a result, the RP/C electrodes deliver a reversible specific capacity of ≈750 mA h g−1 and exhibit a high‐rate capability (≈300 mA h g−1 at 1000 mA g−1). RP/C full cells using potassium manganese hexacyanoferrate as cathode show a long cycling life (680 cycles) at a current density of 1000 mA g−1, in addition, a pouch‐type battery is built to demonstrate practical applications. Red phosphorus (RP) is activated for potassium‐ion battery anodes via a facile wet‐ball milling process. Supported by the conductive network composed of multiwall carbon nanotubes and Ketjen black, full cells comprising an RP/C anode and a potassium manganese hexacyanoferrate cathode show a high specific energy density (193 Wh kg−1) that is a high value for K‐ion full cells.